KAJIAN TAMAN PINTAR SEBAGAI RUANG TERBUKA PUBLIK DALAM KONTEKS KOTA LAYAK ANAK DI KOTA YOGYAKARTA - Suhartini Suhartini (Fakultas Teknik Universitas Khairun, 2022)
Taman Pintar is one of the playgrounds provided by the Yogyakarta City Government. Taman Pintar combines recreational and educational tourist attractions in one location. On a city scale, Taman Pintar becomes a planned public space that provides play facilities for children. The purpose of the study is to determine the system of setting public space used by children both in planned public spaces of Taman Pintar, so that factors were obtained that influence the use of child-friendly public spaces in Yogyakarta City. This research is qualitative with a case study method. Data collection was carried out by accidental sampling with children and parents. Analysis techniques based on matchmaking patterns then build case descriptions. The results shows the system of setting Taman Pintar is located in a strategic location in the center of city center, served by public transportation routes, there are diverse play facilities with a design of laying close to each other, easy accessibility, visitors feel comfortable, children feel safe and are not afraid to be in Taman Pintar. These six factors affect Taman Pintar as a public open space that is friendly with children.